Correction: Niu et al. Prioritization of Renewable Energy Alternatives for China by Using a Hybrid FMCDM Methodology with Uncertain Information. Sustainability 2020, 12, 4649 - Niu, Dongxiao; Zhen, Hao; Yu, Min; Wang, Keke; Sun, Lijie; Xu, Xiaomin (Sustainability, 2022)
The authors would like to make the following corrections to the published paper [...]